PERANAN KEBUDAYAAN DALAM PENCITRAAN PARIWISATA BALI - Malik, Farmawaty (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
The information and publication about Bali have been done since 1914. The image of Bali has already been imprinted in tourist’s mind in the last 100 years. Then what is the role of culture on Bali tourism image? The aim of this study is to observe Balinese daily activities that preserve the Balinese culture as well as their integrity and identity. The research method used is ethnography approach supported by references about image. The research expected to give awareness and special Recommendations to Deputy for Destination Development and Tourism Industry that the positive strength of preserved culture in Bali could be an example and benchmark for other regions. Bali is a powerful and important brand image from Indonesia.